Medida anatômica em cadáveres como referência para a cirurgia endoscópica dos seios paranasais em tomografias computadorizadas - Andressa Vinha Zanuncio (2020)
Nasal rigid endoscope-guided sinus surgery (endoscopic sinus surgery) is used to treat sinus, nasal cavity, and skull base diseases. Detailed knowledge of the nasal anatomy is important for safe and efficient surgery, minimizing risks and complications. The objective of this study is to measure the distance from the posterior wall of the maxillary sinus to the anterior skull base in anatomic dissection, and an analogous distance in computed tomography (CT scan) and to compare them after each isolated analysis and between the right and left sides of the nasal cavity, aiming to detail a new anatomical reference distance. Cadavers object of this study were patients from the São João de Deus Health Complex (CSSJD). After the family authorization, a sinus CT scan was performed with subsequent sinuses dissection. Distances were calculated between the most upper and medial point of the posterior wall of the maxillary sinus (A point) up to the point where the skull base deflects to form the anterior sphenoid wall - Δ90º (B point). CT scan measurements, called AB-tomography, were performed by two radiologists in the axial plane in multislice tomography, 16 GE channels, with posterior multiplanar reconstruction (MPR) in the sagittal plane with 0.65 mm thickness to visualize the two points of interest in the same image. The measure, called AB-dissection, was performed by the researcher in the nasal cavities of 51 cadavers, all over 18 years old, after dissection. All measurements on CT scan and dissections were lower than 1,5cm. There was an excellent level of agreement among both radiologists. The measures are positively correlated. The 1cm increase in the AB-tomography measure corresponds to the 1.08 cm increase at the right and 1.07 cm to the left in the AB-dissection measure. The measurements obtained via CT scan may be considered a reliable tool to promote safe and effective access of the paranasal sinuses, matching to the distance that should be dissected until the anterior skull base.